Zygomatic Complex Fractures in Patients with Oral and Maxillofacial Trauma; Prevalence and Causes at a Tertiary Care Center (Medical Forum Monthly, 2024)
Objective: To find out the prevalence and causes of zygomatic complex fractures in patients with oral and maxillofacial trauma at a tertiary care center.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Oral Biology / Oral Medicine, Bakhtawar Amin Medical and Dental College, Multan from March 2023 to May 2024.Methods: A total of 120 patients from the outpatient department who presented with oral and maxillofacial injuries and were of either gender were included in this research and on contrary the individuals who presented with injuries from bomb blasts or gunshot wounds were excluded from the study. All the data was analyzed by using SPSS Version 22.Results: A total of 120 individuals who presented with maxillofacial trauma were studied. The patients’ average age was 31.522 years. The age group of 20 to 30 years old comprised the majority of patients in our research, making approximately 62% of all patients. There were 12.5% of patients in the age category of 31 to 40 years old and 25% of patients in the age group of 41 to 50 years old. Gender distribution showed that there was a preponderance of male patients, making up 75% of the total count while female patients made up 25% of it. 40 cases (33.3%) of zygomatic complex fractures were reported. The most prevalent etiology of zygomatic complex fractures was road traffic accidents 18 (45%) cases, followed by falls from heights, 13 (32.5%) cases. Since the majority of patients with zygomatic traumas were in the demographic range of 20 to 30, we found that this was the most susceptible age group for zygomatic complex fractures (p < 0.05). The gender-wise correlation with zygomatic fractures showed that, in comparison to female gender, male gender was more affected (p < 0.05).Conclusion: Our research leads us to the conclusion that traffic accidents are the most frequent etiological cause for zygomaticomaxillary complex fractures.